The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-83582012000200023
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing activity of herbicides at reduced rate on Emex spinosa campd. with adjuvants

Abstract: -In pot experiments, two adjuvants were evaluated for their efficacy in enhancing activity of five herbicides applied at reduced rates (75% of the recommended rates) on Emex spinosa at the cotyledon-leaf and at the two-to four-leaf stage. Herbicides (at recommended rates) including fluroxypyr+MCPA at 450 g a.i. ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…However, the other three herbicides viz., iodosulfuron-methyl sodium, mesosulfuron-methyl + iodosulfuronmethyl sodium and fluroxypyr + tribenuron-methyl + clopyralid could be ranked in the second, third and fourth positions, respectively, in this regard. Our findings are parallel to those of Javaid et al (2012), who recorded 100 % control of Emex spinose with bromoxynil+ MCPA applied at a reduced rate with alkyl ether sulfate sodium salt.…”
Section: Weed Density (M -2 )supporting
confidence: 89%
“…However, the other three herbicides viz., iodosulfuron-methyl sodium, mesosulfuron-methyl + iodosulfuronmethyl sodium and fluroxypyr + tribenuron-methyl + clopyralid could be ranked in the second, third and fourth positions, respectively, in this regard. Our findings are parallel to those of Javaid et al (2012), who recorded 100 % control of Emex spinose with bromoxynil+ MCPA applied at a reduced rate with alkyl ether sulfate sodium salt.…”
Section: Weed Density (M -2 )supporting
confidence: 89%
“…The higher weed control with the addition of adjuvant can be attributed to greater absorption of herbicide by weeds (Tahir et al, 2011;Tanveer et al, 2015). These results are supported by Javaid et al (2012), who stated that an effective adjuvant activator enhances the penetration of the herbicide and increase weed control efficacy. More weed control efficiency at narrow row spacing might be due to more weed crop competition, which reduced weed growth and weed biomass, ultimately resulting in more weed control efficiency (Padilha et al, 2016).…”
Section: Weed Control Efficiency Of C Arvensis T Portulacastrum Anmentioning
confidence: 56%
“…Adjuvants increase herbicide efficacy by increasing herbicide retention on the plant surface, more penetration through the cuticle and alteration of the surface tension, pH, thickness and distribution of spray solution (Zadorozhny, 2004). Javaid et al (2012) reported that alkyl ether sulphate increased the efficacy of post-emergence herbicides and reduced herbicide rates without compensating weed control. However, effective weed control at reduced herbicide rates depends upon the type of herbicides being applied, type of adjuvant and characteristic of target weed species (Bunting et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, at lateral stages of parthenium growth, this treatment has less death rate of parthenium. Javaid et al (2012) did a pot trial to assess the potential of two adjuvants to find their adequacy in enhancing the action of five herbicides sprayed at suggested dosage at 2-4 leaf periods and at less dosage (75%) on Emex spinosa at foliage-leaf and 2-4 leaf stage. Expansion of AES as adjuvant to diminished rate of carfentrazone ethyl and fluroxypyr + MCPA updated their reasonability, with biomass decline and 100% death of E. spinosa.…”
Section: Application Of Adjuvantmentioning
confidence: 99%